Pemanfaatan Teknologi Realitas Tertambah sebagai Media Pembelajaran Jenis Ikan Air Tawar pada Anak Usia Dini Berbasis Android - Yudistira Anugrah Saputra; Henri Septanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Using Augmented Reality technology, this study aims to create an alternative medium for teaching young children about bream species. Augmented Reality is a technology that permits users to perceive three-dimensional objects (3D). Multimedia Development Life Cycle is used as the software development methodology (MDLC). This method is comprised of the stages of conception, design, material collection, assembly, testing, and distribution. To develop the learning application utilizing Unity and C#. This study yields learning applications of bream species for the Android operating system that can detect markers and display nine species of fish as three-dimensional objects (3D) along with information about each species.